Pediatric Hypertension (Springer International Publishing, 2018)
The fourth edition of this book is the most comprehensive major reference work on hypertension in children and adolescents. Since the publication of the previous edition, there have been notable changes in the field, with the arrival of new evidence of the long-term sequelae of hypertension in youth, an evidence-based review of the value of routine BP screening in children and adolescents, and further evidence of the cardiovascular consequences of the childhood obesity epidemic. This expanded edition covers these new findings, while featuring new chapters on such timely topics as routine blood pressure screening, hypertension in late adolescents/young adults, and current pediatric hypertension research. The reference work also includes thorough updates on chapters from the previous edition, as well as new clinical practice guidelines for childhood hypertension, which have not been revised since 2004. Written by experts in the field, Pediatric Hypertension, Fourth Edition is the definitive resource for clinicians and researchers interested in childhood hypertension. .